Integrated field and office tools for bridge management - Siddiqui, Mohshin; Juni, Emil; Adams, Teresa M.; Dzienkowski, James (Wisconsin Highway Research Program, 2004)
The Wisconsin Department of Transportation (WisDOT) Bureau of Structures data consolidation project brings together all bridge-related data into a single Highway Structure Inventory System (HSIS) data warehouse including inventory, inspection and maintenance records, and maintenance cost. With the new HSIS, WisDOT's interactive bridge inspection forms and data procedures became incompatible. The HSIS presented a timely opportunity to investigate alternative data collection tools that are practicable in the field. This research investigates the use of field data tools for bridge inspection. Bridge inspectors participated in identifying functional requirements leading to an assembly of field tools including Tablet PC with shoulder carrying case, noise-canceling headset microphone, and tethered pen. Bridge inspectors from 6 districts volunteered for training to use the handwriting and speech recognition technologies and then to test the tools for practical use in bridge inspection. This report presents the tool selection process, training, and evaluation of technology adoption and economic benefits. The report includes an evaluation of alternative technologies choices along with recommendation for full deployment.
62 p.
Keywords: Data warehouses; Data collection; Inspection; Maintenance; Deployment; Bridges; Records management; Technological innovations; Inventory; Alternatives analysis; Costs; Bridge management systems; Training